Liver transplantation in a child with sclerosing cholangitis due to Langerhans cell histiocytosis: a case report - Wang, Xue-Lian; Fang, Chun-Xiao; Chen, Min-Xia; Yang, Hua-Mei; She, Lan-Hui; Gong, Yu; Xu, Yi; Xiao, Wei-Qiang; Tian, Jin-Sheng; Ai, Bin; Huang, Li; Li, Xu-Fang (Frontiers in Pediatrics, 2024)
Background: Langerhans cell histiocytosis (LCH) is a systemic neoplasia with diverse clinical manifestations, predominantly affecting bone and skin. However, in children, LCH presenting primarily with cholestasis is rare.Case Summary: We present the case of a 22-month-old boy who was admitted to our hospital with a history of intermittent fever and abdominal distension for over 2 months, and jaundice for over 1 month. Prior to admission, the child had been managed with anti-infective and anti-inflammatory drugs and supportive care at multiple hospitals without significant improvement. He was then referred to our facility for further treatment. Upon admission, a series of laboratory tests, imaging studies, and pathological examinations were conducted, revealing the presence of diabetes insipidus, sclerosing cholangitis (SC), and liver cirrhosis. These findings led to a clinical diagnosis of LCH. Given the absence of definitive pathological evidence, his progression to decompensated liver cirrhosis and his pronounced growth retardation, the child was deemed a candidate for living donor liver transplantation. Following the liver transplant, pathological examination of the explanted liver tissue confirmed the clinical diagnosis of LCH. The child received postoperative chemotherapy, which resolved his systemic symptoms and normalized liver function. There was no evidence of LCH recurrence. The symptoms of diabetes insipidus were controlled with desmopressin acetate, however, the existing destructive lesions in the pituitary gland persisted.Conclusion: Sclerosing cholangitis is a late and severe form of liver involvement in LCH that may be accompanied by lesions in other tissues or organs. Along with pathological evidence, a diagnosis should be made based on characteristic rashes, osteolytic lesions, and thickening of the pituitary stalk. In children with LCH complicated by SC for whom pathological diagnostic evidence cannot be obtained, liver transplantation may be considered once signs of decompensated liver cirrhosis appear, followed by systemic chemotherapy to control active disease. This strategy represents a therapeutic approach with the potential to achieve a better prognosis in children with LCH.